Aqueous Cathodic Deposition: Aqueously Cathodic Deposition of ZIF‐8 Membranes for Superior Propylene/Propane Separation (Adv. Funct. Mater. 7/2020). (12th February 2020) - Wei, Ruicong; Chi, Heng‐Yu; Li, Xiang; Lu, Dongwei; Wan, Yi; Yang, Chih‐Wen; Lai, Zhiping
Abstract : In article number 1907089, Zhiping Lai and co‐workers develop an aqueous cathodic deposition method to fabricate ZIF‐8 membranes. The membrane grows under a current, which provides a self‐healing mechanism, leading to an ultrathin and defect‐free membrane that shows excellent performance in propylene/propane separation.